Theoretical Legal Assumptions for the United Nations Security Council Reform - Jorge Luis Silva González,; Orelvis Gener Crespo,; Pedro Alejandro Vigil García, (Technium Social Sciences Journal, 2021)
The United Nation Security Council, although it has been the most reformed organ of the Organization, does not currently respond to the claims of democracy of the international community. In this regard, this article proposes four theoretical legal assumptions that should underpin the democratization of the aforementioned organ, regarding the structure and operation established by the UN Charter. The use of applicable methods in the Legal Sciences allowed the formulation of the postulates, among them: the recognition of the perspective of democracy in the UN Charter, and the transformation of the voting system into non-procedural matters and in relation to the processes of reform and revision of the UN Charter.